Implications of farming trends for agricultural research in mainland Southeast Asia - Cramb, R.A.; Gray, G.D.; Gummert, M.; Haefele, S.M.; Lefroy, Rod D.B.; Newby, Jonathan Craig; Stür, Werner W.; Warr, P. (Australian Centre for International Agricultural Research, 2015)
For centuries, the populations of Mainland Southeast Asia (MSEA) have endured material poverty, particularly in rural areas and among subsistence-oriented, rice-farming households. In the 20th century in particular, the impact of colonialism, war, and collectivist regimes exacerbated the poverty of rural communities. In recent decades, however, increased economic growth in MSEA countries has been associated with a marked reduction in poverty levels. As shown in Chapter 2, reduction of poverty within rural areas is the main source of this significant reduction in aggregate poverty in MSEA. The achievement of high rates of poverty reduction has derived from high rates of economic growth, especially in the agricultural sector. The real price of food is also an important determinant of poverty incidence, with lower prices helping to reduce both rural and urban poverty. Hence policies and institutions that promote increased agricultural productivity and do not significantly raise the price of food are most likely to maximise the rate of poverty reduction in the coming decades – both in rural areas and in the total population. The focus of this monograph has been on identifying the options for subsistence-oriented (i.e., rice-farming) rural households to capitalise on the poverty-reducing potential of the economic growth that is transforming the MSEA region. In this chapter we review the farming trends in the region and highlight the implications for agricultural research in coming decades.